A novel probe based on phenylboronic acid functionalized carbon nanotubes for ultrasensitive carbohydrate determination in biofluids and semi-solid biotissues. Issue 2 (1st December 2015) - Chen, Guosheng; Qiu, Junlang; Xu, Jianqiao; Fang, Xu'an; Liu, Yan; Liu, Shuqin; Wei, Songbo; Jiang, Ruifen; Luan, Tiangang; Zeng, Feng; Zhu, Fang; Ouyang, Gangfeng
Abstract : An ultrasensitive SPME probe based on phenylboronic acid functionalized CNTs is applied for direct in vitro or in vivo recognition of carbohydrates in biofluids as well as semi-solid biotissues. Abstract : Carbohydrates are known to be involved in a wide range of biological and pathological processes. However, due to the presence of multiple hydroxyl groups, carbohydrate recognition is a particular challenge. Herein, we reported an ultrasensitive solid-phase microextraction (SPME) probe based on phenylboronic acid (PBA) functionalized carbon nanotubes (CNTs) for direct in vitro or in vivo recognition of carbohydrates in biofluids as well as semi-solid biotissues. The coating of the proposed probe possessed a 3D interconnected porous architecture formed by the stacking of CNTs. As a result, the binding capacity toward carbohydrates was excellent. The proposed approach was demonstrated to be much superior to most carbohydrate sensors, including higher sensitivity, wider linear range, and excellent qualitative ability in multi-carbohydrate systems. Thus, this approach opens up new avenues for the facile and efficient recognition of carbohydrates for important applications such as glycomics.